Perceptions of native and non-native English varieties by Chinese EFL learners: an investigation of the effects of study abroad - Fang, J (2021)
This study investigated Chinese EFL learners’ perceptions of different varieties of English, and compared the perceptions of learners with and without experience of Study Abroad (SA) in Anglophone countries. A total of ninety Chinese university students majoring in language studies participated in an online survey. They listened to seven English varieties (RP, Glaswegian, Liverpudlian, Indian, Italian, Chinese and Malaysian) and evaluated these using four criteria (comprehensibility, social-attractiveness, foreign-accentedness and variety recognition) on a series of six-point Likert scales and two open-ended questions. According to statistical analysis, all participants regarded the standard variety (RP) and the local variety (Chinese) highly in terms of comprehensibility and social-attractiveness. Participants were generally sensitive towards the native and non-native accentedness. With regard to variety recognition, participants consistently and accurately identified the standard variety and the local Chinese variety. Participants were less certain about the origin of the regional UK varieties and the international varieties. When adding in the factor of different learning contexts (at home and Study Abroad), the results revealed that study abroad in the UK has a positive influence on participants’ perceptions of international and regional UK varieties. Listeners with study abroad experience perceived Italian-accented speech as more comprehensible and more attractive and they were more likely to accurately identify the origin of regional UK varieties. The findings imply that study abroad may have value in helping learners to understand and accept non-standard or unfamiliar varieties of English. Based on participants’ responses, there were highly positive attitudes towards linguistic diversity and willingness to learn nonstandard varieties, suggesting a demand for the inclusion of nonstandard varieties in the classroom.